Linguistic and cultural features of Ukrainian mimicry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the specific implementation of linguistic and cultural Ukrainian facial reactions. It also investigates the structure and semantics of phrases and proverbs related to native speakers perceptions of nonverbal communication. This research has shown that these set expressions allow reconstructing the options of interpersonal interaction due to facial expressions and body movements. At the same time these linguistic units represent the mental component of communication and its national and cultural character.
Keywords: idiom; nonverbal communication; body language and mentality